Comparison Algorithm Kernels on Support Vector Machine (SVM) To Compare The Trend Curves with Curves Online Forex Trading - irfan abbas (Universitas PGRI Semarang, 2016)
At this time, the players Forex Trading generally still use the data exchange in the form of a Forex Trading figures from different sources. Thus they only receive or know the data rate of a Forex Trading prevailing at the time just so difficult to analyze or predict exchange rate movements future. Forex players usually use the indicators to enable them to analyze and memperdiksi future value. Indicator is a decision making tool. Trading forex is trading currency of a country, the other country's currency. Trading took place globally between the financial centers of the world with the involvement of the world's major banks as the major transaction. Trading Forex offers profitable investment type with a small capital and high profit, with relatively small capital can earn profits doubled. This is due to the forex trading systems exist leverage which the invested capital will be doubled if the predicted results of buy / sell is accurate, but Trading Forex having high risk level, but by knowing the right time to trade (buy or sell), the losses can be avoided. Traders who invest in the foreign exchange market is expected to have the ability to analyze the circumstances and situations in predicting the difference in currency exchange rates. Forex price movements that form the pattern (curve) up and down greatly assist traders in making decisions. The movement of the curve used as an indicator in the decision to purchase (buy) or sell (sell). This study compares (Comparation) type algorithm kernel on Support Vector Machine (SVM) to predict the movement of the curve in live time trading forex using the data GBPUSD, 1H. Results of research on the study of the results and discussion can be concluded that the Kernel Dot, Kernel Multiquaric, Kernel Neural inappropriately used for data is non-linear in the case of data forex to follow the pattern of trend curves, because curves generated curved linear (straight) and then to type of kernel is the closest curve similar to the curve trend of online forex trading is Anova kernel and kernel radial, a little closer Combination Gaussian kernel, kernel Epachnenikof and to kernel polynomial form a parabolic curve open. key words: Trading Forex, Support Vector Machine, Kernel Anova, Dot Kernel, Kernel Multiquaric, Kernel Neural, Prediction, radial Kernel, Kernel Gaussian Combination, Epachnenikof kernel, polynomial kernel, EURUSD H1